2008
DOI: 10.1038/ajh.2008.196
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Masked Hypertension in Subjects With Prehypertension

Abstract: Among subjects with prehypertension, those with masked hypertension are at higher cardiovascular risk than those with true prehypertension. Out-of-office BP should be known in individuals with prehypertension, preferably by ambulatory BP monitoring or alternatively by home BP measurement, to obtain a better prognostic stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…21 When this is found, further examinations are mandatory because data are remarkably consistent that in masked hypertension (1) there is a greater prevalence and severity of metabolic risk factors, including overweight, dyslipidemia, impaired glucose tolerance, and diabetes mellitus; (2) subclinical cardiac, vascular, or renal damage is more common; (3) the long-term risk of developing sustained hypertension, diabetes mellitus, or left ventricular hypertrophy is 2 to 3 times greater than that of individuals with normal in-and out-of-office BP; and (4) there is also a greater incidence of cardiovascular morbid and fatal events, with an overall risk that is either intermediate or, in some studies, closer to that of sustained hypertension than to true normotension. [95][96][97][98][99][100][101][102][103][104][105][106][107] This represents a sort of a proof of concept of the prognostic impact of ambulatory, and more in general out-of-office BP values vis-à-vis the traditional BP classification based on office BP measurements only.…”
Section: Masked Hypertensionmentioning
confidence: 96%
“…21 When this is found, further examinations are mandatory because data are remarkably consistent that in masked hypertension (1) there is a greater prevalence and severity of metabolic risk factors, including overweight, dyslipidemia, impaired glucose tolerance, and diabetes mellitus; (2) subclinical cardiac, vascular, or renal damage is more common; (3) the long-term risk of developing sustained hypertension, diabetes mellitus, or left ventricular hypertrophy is 2 to 3 times greater than that of individuals with normal in-and out-of-office BP; and (4) there is also a greater incidence of cardiovascular morbid and fatal events, with an overall risk that is either intermediate or, in some studies, closer to that of sustained hypertension than to true normotension. [95][96][97][98][99][100][101][102][103][104][105][106][107] This represents a sort of a proof of concept of the prognostic impact of ambulatory, and more in general out-of-office BP values vis-à-vis the traditional BP classification based on office BP measurements only.…”
Section: Masked Hypertensionmentioning
confidence: 96%
“…Presently, scarce data exist from prior studies as to whether MHT adds prognostic information in individuals with PHT. In what to our knowledge is the only published study to examine the predictive value of MHT for CVD events in participants with PHT, Pierdomenico et al 29 found that in participants with PHT, MHT was associated with a significantly higher rate of CVD events, compared to those participants without MHT ("true PHT"). This study was limited by a small number of events (18 events in MHT and PHT vs. 11 events in true PHT) and potentially incomplete examination of confounders such as male gender.…”
Section: Masked Hypertension and Prehypertensionmentioning
confidence: 99%
“…4,[21][22][23][24][25] Both conditions are commonly observed in the same individual and are associated with additive effects in the occurrence of cardiovascular events. 26 However, the risk factors and mechanisms leading to these conditions are not completely understood. 27 OSA may be associated with prehypertension and masked hypertension for at least 3 reasons.…”
Section: Drager Et Al Osa Prehypertension and Masked Hypertensionmentioning
confidence: 99%